Find solutions to your problems with the help of IDNLearn.com's knowledgeable users. Ask anything and get well-informed, reliable answers from our knowledgeable community members.
Sagot :
Certainly! Let's complete the table step by step according to the given function rule [tex]\( y = 4 - \frac{3}{4} x \)[/tex].
1. Determine [tex]\( y \)[/tex] when [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 4 - \frac{3}{4} \times 4 \][/tex]
Substituting [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 4 - \frac{3 \times 4}{4} = 4 - 3 = 1 \][/tex]
Thus, when [tex]\( x = 4 \)[/tex], [tex]\( y = 1 \)[/tex].
2. Determine [tex]\( y \)[/tex] when [tex]\( x = 8 \)[/tex]:
[tex]\[ y = 4 - \frac{3}{4} \times 8 \][/tex]
Substituting [tex]\( x = 8 \)[/tex]:
[tex]\[ y = 4 - \frac{3 \times 8}{4} = 4 - 6 = -2 \][/tex]
Thus, when [tex]\( x = 8 \)[/tex], [tex]\( y = -2 \)[/tex].
3. Determine [tex]\( y \)[/tex] when [tex]\( x = 12 \)[/tex]:
[tex]\[ y = 4 - \frac{3}{4} \times 12 \][/tex]
Substituting [tex]\( x = 12 \)[/tex]:
[tex]\[ y = 4 - \frac{3 \times 12}{4} = 4 - 9 = -5 \][/tex]
Thus, when [tex]\( x = 12 \)[/tex], [tex]\( y = -5 \)[/tex].
Now, let's fill in the table with these values:
[tex]\[ \begin{tabular}{c|ccccc} $x$ & -4 & 0 & 4 & 8 & 12 \\ \hline $y$ & 7 & 4 & 1 & -2 & -5 \\ \end{tabular} \][/tex]
So the completed table is:
[tex]\[ \begin{tabular}{c|ccccc} $x$ & -4 & 0 & 4 & 8 & 12 \\ \hline $y$ & 7 & 4 & 1 & -2 & -5 \\ \end{tabular} \][/tex]
1. Determine [tex]\( y \)[/tex] when [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 4 - \frac{3}{4} \times 4 \][/tex]
Substituting [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 4 - \frac{3 \times 4}{4} = 4 - 3 = 1 \][/tex]
Thus, when [tex]\( x = 4 \)[/tex], [tex]\( y = 1 \)[/tex].
2. Determine [tex]\( y \)[/tex] when [tex]\( x = 8 \)[/tex]:
[tex]\[ y = 4 - \frac{3}{4} \times 8 \][/tex]
Substituting [tex]\( x = 8 \)[/tex]:
[tex]\[ y = 4 - \frac{3 \times 8}{4} = 4 - 6 = -2 \][/tex]
Thus, when [tex]\( x = 8 \)[/tex], [tex]\( y = -2 \)[/tex].
3. Determine [tex]\( y \)[/tex] when [tex]\( x = 12 \)[/tex]:
[tex]\[ y = 4 - \frac{3}{4} \times 12 \][/tex]
Substituting [tex]\( x = 12 \)[/tex]:
[tex]\[ y = 4 - \frac{3 \times 12}{4} = 4 - 9 = -5 \][/tex]
Thus, when [tex]\( x = 12 \)[/tex], [tex]\( y = -5 \)[/tex].
Now, let's fill in the table with these values:
[tex]\[ \begin{tabular}{c|ccccc} $x$ & -4 & 0 & 4 & 8 & 12 \\ \hline $y$ & 7 & 4 & 1 & -2 & -5 \\ \end{tabular} \][/tex]
So the completed table is:
[tex]\[ \begin{tabular}{c|ccccc} $x$ & -4 & 0 & 4 & 8 & 12 \\ \hline $y$ & 7 & 4 & 1 & -2 & -5 \\ \end{tabular} \][/tex]
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! IDNLearn.com is committed to providing accurate answers. Thanks for stopping by, and see you next time for more solutions.